2020
DOI: 10.1097/md.0000000000021646
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stem cell therapy and comprehensive physical therapy in motor and non-motor symptoms in patients with multiple sclerosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In brief, this study demonstrated the potential of NSCs to induce anti-inflammatory responses and provide neuroprotection and promote endogenous neurogenesis resulting in the reversal of EAE clinical symptoms and repair of the damaged CNS. Although there have been a number of clinical trials utilizing autologous bone marrow MSCs and umbilical cord-derived MSCs, the results are not always conclusive [66][67][68]. Furthermore, most of these studies were limited to phase I and II trials due to the limited availability of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, this study demonstrated the potential of NSCs to induce anti-inflammatory responses and provide neuroprotection and promote endogenous neurogenesis resulting in the reversal of EAE clinical symptoms and repair of the damaged CNS. Although there have been a number of clinical trials utilizing autologous bone marrow MSCs and umbilical cord-derived MSCs, the results are not always conclusive [66][67][68]. Furthermore, most of these studies were limited to phase I and II trials due to the limited availability of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, there was improvement in the quality of life measures one month following treatment; however, the participants reported similar levels of pain one year after treatment (54,55). Furthermore, most of these studies were limited to phase I and II trials due to limited availability of cells.…”
Section: Resultsmentioning
confidence: 99%
“…The most encouraging results were for CD/IBD, in which peri‐fistula injections of either autologous or allogenic BMMSCs or allogenic AdMSCs promoted healing of perianal fistulas 83‐86 ; intravenous injection of allogenic WJUCMSCs to CD and ulcerative colitis (UC) patients also reduced mucosal inflammation 87,88 . The six published reports using autologous BMMSCs administered intravenously or intrathecally for MS demonstrated safety and some non‐significant reduction of inflammatory parameters 89‐94 ; two other reports utilized allogeneic WJUCMSCs, with one study still ongoing 95 and one seeing benefit in several clinical parameters 96 . For RA, both autologous BMMSCs and allogenic AdMSCs were well tolerated and trended toward efficacy 97,98 .…”
Section: Current Clinical Trials Of Msct For Immune‐related Diseases: Specific Indicationsmentioning
confidence: 99%